Investigation of the Causes of Prematurity and Neonatal Death Admitted to Hospitals in Ardabil City - Faramarz Ajri-Khamesloo; Lida Ghorbani; Aziz Kamran; Sevin Fattahi (Patient Safety and Quality Improvement Journal)
Introduction: Premature delivery is the delivery of a baby before the completion of 37 weeks of pregnancy. Premature birth is the main cause of infant mortality. Several risk factors and causes for preterm delivery and its mortality have been stated. The aim of this study was to investigate the causes of prematurity and death of neonates hospitalized in Ardabil city hospitals. Materials and Methods: In this cross-sectional study, 500 premature births which selected randomly were evaluated between September 2022 and September 2023. The required information, including the demographic characteristics of the baby and parents, birth weight, cause of preterm delivery and related factors, and the cause of infant death, were collected by examining the patient files in the hospital archive. Results: 273 babies (55.6%) were boys. Preeclampsia and high blood pressure (21.8%), followed by gestational diabetes (10.6%) and overt diabetes (6.2%) were the most common underlying diseases in mothers. The difference in the final outcome of death or life in babies born with different indications and etiologies of preterm delivery was significant. Conclusion: Pulmonary-respiratory causes were the most common causes involved in the death of preterm infants studied. The etiology of preterm delivery was significantly related to the outcome of mortality in the studied preterm infants and its causes.